Exploring the causal involvement of the rIPL and white matter interindividual variability in spatial orienting and consciousness - Joaquín J. Ramírez-Guerrero; Cristina Narganes-Pineda; Mar Martín-Signes; Ana B. Chica (NeuroImage)
Background: Spatial attention enables the selection of relevant over irrelevant stimuli through dorsal and ventral fronto-parietal networks. These networks are connected through long white matter tracts, such as the superior longitudinal fasciculus (SLF) and the Inferior Fronto-Occipital fasciculus (IFOF). Objective/hypothesis: The main purpose of this study was to explore, in healthy participants, the causal role of the right Inferior Parietal Lobe (rIPL) in spatial orienting and conscious perception. We also explored how interindividual differences in the microstructural properties of white matter were related to the effects of transcranial magnetic stimulation (TMS) and, secondarily, to attentional orienting effects in the control stimulation condition. Methods: Participants (n=51) performed a behavioural task involving the detection of a visual stimulus at the threshold of consciousness, preceded by either central (endogenous) or peripheral (exogenous) cues. After cue onset, a burst of TMS pulses was applied over the rIPL or a control active region (vertex). White matter properties were explored through diffusion-weighted imaging tractography and whole-brain NODDI analysis. Results: TMS over the rIPL (compared to the control condition) did not modulate spatial attention nor conscious perception, but it decreased accuracy when attention was endogenously oriented (compared to the exogenous condition) and speeded up reaction times when targets were presented in the attended right hemifield (compared to the left hemifield). Part of the variability in the TMS and attentional orienting effects were explained by the integrity of the SLF and the IFOF. Conclusions: Individual variability in attentional orienting effects was associated with the anatomical links between attentional networks. Negative correlations between TMS effects and relevant white matter tracts were interpreted as compensatory mechanisms, while positive correlations with tracts innervating the stimulated area could reflect a TMS signal propagation effect. These results will contribute to the understanding of the role of white matter variability in the susceptibility to neuromodulation, with potential implications for research and clinical treatment.